Which expression is equivalent to 3(4m – 2) – 2(m + 5) A. 10m – 16 B. 14m + 4 C. -16m + 10 D

Question

Which expression is equivalent to 3(4m – 2) – 2(m + 5)

A. 10m – 16

B. 14m + 4

C. -16m + 10

D. 12m – 6

in progress 0
Vân Khánh 1 year 2021-07-27T16:04:03+00:00 2 Answers 9 views 0

Answers ( )

    0
    2021-07-27T16:05:08+00:00

    Answer:

    A. 10m – 16

    Step-by-step explanation:

    First, distribute 3 to all terms within the corresponding parenthesis, and -2 likewise:

    3(4m – 2) =

    3 * 4m = 12m

    3 * -2 = -6

    3(4m – 2) = 12m – 6

    -2(m + 5) =

    -2 * m = -2m

    -2 * 5 = -10

    -2(m + 5) = -2m -10

    Combine like terms:

    12m – 6  -2m – 10

    12m – 2m – 6 – 10

    (12m – 2m) + (-6 – 10)

    10m – 16

    A. 10m – 16 is your answer.

    ~

    0
    2021-07-27T16:05:52+00:00

    Answer:

    10 m – 16 (Answer A)

    Step-by-step explanation:

    We use distributive property to eliminate parenthesis:

    12 m – 6 – 2 m -10

    and now combine like terms:

    [12 m – 2 m] – 6 – 10

    10 m – 16

    Therefore, answer option A.  is the correct one

Leave an answer

Browse

Giải phương trình 1 ẩn: x + 2 - 2(x + 1) = -x . Hỏi x = ? ( )